Influence of the pinch-point-temperature difference on the performance of the Preheat-parallel configuration for a low-temperature geothermally-fed CHP. (September 2017) - Van Erdeweghe, Sarah; Van Bael, Johan; Laenen, Ben; D'haeseleer, William
Abstract: In this work, we investigate the performance of the so-called Preheat-parallel CHP configuration, for the connection to a thermal network (TN). A low-temperature geothermal source (130°C), and the connection to a 75°C/50°C and a 75°C/35°C thermal network are considered. For a pure parallel CHP configuration, the brine delivers heat to the ORC and the thermal network in parallel. However, after having delivered heat to the ORC, the brine in the ORC branch still contains some energy which is not used. The Preheat-parallel configuration utilizes this heat to preheat the TN water before it enters the parallel branch, where the TN water is heated to the required supply temperature. The Preheat-parallel configuration is especially favorable when connected to a thermal network with a low return temperature, a large temperature difference between supply and return temperatures—thereby exploiting the preheating-effect—and for high heat demands. In this paper, we focus on the effect of the pinch-point-temperature difference (∆Tpinch ) on the plant performance. ∆Tpinch is directly related with the size and cost of the heat exchangers and strongly influences the preheating-effect, which is the most characteristic feature of the Preheat-parallel configuration. First, we present the results of a detailed sensitivity analysis of ∆Tpinch . A higher ∆Tpinch results in a lower preheating-effect, a lower net power output and, correspondingly, lower plant efficiency. Furthermore, we compare the performance of the Preheat-parallel configuration with the convenient parallel and series CHP configurations. For all three configurations, the performance decreases with an increase of ∆Tpinch . For the considered thermal network requirements, the net power generation is the highest for the Preheat-parallel configuration. With respect to the parallel configuration, the gain in net power generation stays approximately constant (75°C/35°C TN) or decreases (75°C/50°C TN) with the imposed pinch-point-temperature difference. With respect to the series configuration, the gain in net power generation increases for a higher value of ∆Tpinch . This means that the impact of ∆Tpinch is the biggest for the series configuration, followed by the Preheat-parallel configuration, and that the impact on the performance of the parallel configuration is the smallest.